Criação e corpo sem órgãos - Maia, Paulo Carneiro (2018)
The following work revolves around the notion of Body Without Organs as it appears in Artaud and is taken up by Deleuze, Guattari and Uno. Going through different plans proposed by these authors (language, multiplicity, desire, body, theater, genesis, etc.), appears its transversal dimension and the conceptual variation that is its own. In the end, a scenic experimentation gives one of the possible implications in the field of theater